2021
DOI: 10.1016/j.heliyon.2021.e06713
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into country of origin labeling, species authentication and short weighting of commercially sold frozen fish fillets

Abstract: Proper labeling of seafood is important to prevent economic deception and protect public health. The goal of this research was to investigate prepackaged frozen fish for Country of Origin Labeling (COOL) compliance, species labeling, net weights/short weighting, and percent glaze. A total of 111 frozen prepackaged fish fillets were purchased from grocery stores in Southern California (USA). Samples were designated as COOL compliant if they displayed both procurement method and country of origin in accordance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition, certain religions may restrict seafood consumption or prescribe preparation methods [39]. Furthermore, consumers often associate certain countries with high-quality seafood [40]. Preferences may be influenced by perceptions of better taste, freshness, or safety of certain sources.…”
Section: Rq1: What Effect Will An Increase In the Price Of Clams Have...mentioning
confidence: 99%
“…In addition, certain religions may restrict seafood consumption or prescribe preparation methods [39]. Furthermore, consumers often associate certain countries with high-quality seafood [40]. Preferences may be influenced by perceptions of better taste, freshness, or safety of certain sources.…”
Section: Rq1: What Effect Will An Increase In the Price Of Clams Have...mentioning
confidence: 99%
“…Lastly, there have been limited studies of the short weighing of fishery products in the United States. One southern California study showed that 9% of frozen fish were short‐weighted, with an average glaze of 5% (Peterson et al., 2021).…”
Section: Major Safety and Quality Concerns/issuesmentioning
confidence: 99%
“…In summary, current research in the field of COO's effects on consumers' behavior focus mostly on European, USA, Chinese, and Australian markets [5,8,[21][22][23][24], and pay little attention to other geographical markets; in particular, the Central Asian market has been ignored. Global food demand is predicted to increase steeply over the next several decades, particularly in developing countries where rapid population growth and dietary changes may significantly affect the demand for different types of foods [25].…”
Section: Literature Reviewmentioning
confidence: 99%